PENGEMBANGAN BAHAN AJAR IPAS BERBASIS MODEL GOCAR DI SEKOLAH DASAR - Suyanti; rulviana, vivi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This development research has the aim of developing IPAS teaching materials based on the Gocar Model to be feasible and in accordance with the needs of students. The Gocar model is used because it contains activities that involve students, both in terms of activeness and problem-solving challenges. The development model uses ADDIE, the analysis stage includes analyzing the curriculum, needs and characteristics of students, using interviews, observations and questionnaires. The design stage presents a structured and attractive teaching material design according to student needs, including activities interactively, contextually and according to the learning style of students. The results of the validation of material, language and media experts show in the valid group (Aiken's average of 0.82.). The results of implementation were limited to class IV SD N KlagenSerut while the response of teachers and students was very good, seen from the learning outcomes of 77% above KKM. And the evaluation results state that Gocar-based IPAS teaching materials are effectively used in learning.